EVALUATING THE IMPACT OF THE 2015 PARIS AGREEMENT ON CARBON EMISSION REDUCTIONS: A CASE STUDY OF PT. SOLUSI BANGUN ANDALAS - Hasz, Muhammad Ofans; Roesa, Nellyana (Universitas Syiah Kuala, 2024)
This article examines the critical role of corporate social responsibility (CSR) in mitigating carbon emissions within the framework of international law, with a focused case study on PT. Solusi Bangun Andalas (SBA). The research aims to identify the carbon emission reduction initiatives undertaken by SBA as part of its CSR commitments. To achieve this, the study employs a mixed-methods approach, incorporating primary data collected through field research, including interviews with key stakeholders and direct observations, alongside an extensive review of legal literature, regulations, and theoretical frameworks as secondary sources. The findings highlight that the Paris Agreement serves as a pivotal instrument for global climate action, offering a structured approach to addressing climate change by establishing a steadfast goal of limiting global temperature rise to well below 2 degrees Celsius. This international accord not only sets the stage for coordinated efforts to curb carbon emissions but also underscores the responsibility of corporations like SBA in contributing to these global objectives. The implementation of effective carbon reduction strategies aligns with Indonesia's commitment to enhancing its environmental sustainability and fulfilling its international obligations. Ultimately, this study contributes to the broader discourse on the significance of corporate responsibility in fostering environmental stewardship and emphasizes the imperative for businesses to adopt sustainable practices in their operations, ensuring that economic growth does not come at the expense of the planet's health